2018
DOI: 10.18632/oncotarget.v9i51
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Head and neck squamous cell carcinoma (HNSCC) is treated with cisplatin (CDDP) and radiotherapy (RT), and distinct results are observed among patients with similar clinicopathological aspects. This prospective study aimed to investigate whether MLH1 c.-93G>A (rs1800734), MSH2 c.211+9C>G (rs2303426), MSH3 c.3133G>A (rs26279), EXO1 c.1765G>A (rs1047840), and EXO1 c.2270C>T (rs9350) single nucleotide polymorphisms (SNPs) of the mismatch repair (MMR) pathway change side effects and response rate of 90 HNSCC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…A list of selected target proteins that interacted with CARP-1 (614–638) peptide is shown in Table 3 . Of note is the fact that CCAR2 (DBC1; a CARP-1 paralog), Filamin C, and BRAF have been demonstrated to interact with CARP-1 in prior studies by us and others ( 7 , 16 , 26 , 27 ). CARP-1 (614–638) peptide also interacted with MAPK12/p38γ suggesting that MAPK12/p38γ could be the kinase among the MAPKs noted in Table 1 above that functions to transduce CARP-1 T 627 phosphorylation by ADR.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…A list of selected target proteins that interacted with CARP-1 (614–638) peptide is shown in Table 3 . Of note is the fact that CCAR2 (DBC1; a CARP-1 paralog), Filamin C, and BRAF have been demonstrated to interact with CARP-1 in prior studies by us and others ( 7 , 16 , 26 , 27 ). CARP-1 (614–638) peptide also interacted with MAPK12/p38γ suggesting that MAPK12/p38γ could be the kinase among the MAPKs noted in Table 1 above that functions to transduce CARP-1 T 627 phosphorylation by ADR.…”
Section: Resultsmentioning
confidence: 94%
“…Our prior and on-going studies have indicated that DNA damage-inducing genotoxic agents such as ADR, Cisplatin, or CFM compounds promote apoptosis in part by stimulating levels of CARP-1, phosphorylated SAPKs p38α/β and JNK1/2, cleaved PARP, and activated caspases-3, and -8 ( 7 16 ). Knockdown of CARP-1 or pharmacological inhibition of caspase-3 and -8 abrogated apoptosis by ADR, CFM compounds, or EGFR TKIs ( 7 , 9 , 11 , 14 , 16 ). Moreover, expression of CARP-1 with in-frame deletion of amino acids 600-650 (CARP-1 Δ600-650) also abrogated apoptosis by ADR and CFM compound ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations